The Yellow Emperor Culture and the Yellow River Culture - Xu Guangchun (Contemporary Social Sciences, 2016)
As long as we have a thorough understanding of the Yellow Emperor culture and the Yellow River culture, we can grasp the mainstream essence, root and excellence of the traditional Chinese cultures. Thus we will have a better understanding of the history and reality of the Chinese nation and that of Henan Province. We will be able to better inherit and carry forward the fine traditional Chinese cultures, and better construct and promote cultural prosperity with Chinese characteristics, so as to benefit the Chinese people, influence international society and advance cultural progress.